2014
DOI: 10.1017/s1368980014001888
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of anaemia during pregnancy: a study to evaluate the contribution of iron deficiency and common infections in pregnant Ugandan women

Abstract: Objective: To describe the aetiology of anaemia in pregnant Ugandan women and explore Fe deficiency and common infections as contributors to anaemia in this population. Design: Cross-sectional study in which Hb, ferritin, transferrin receptor (sTfR), C-reactive protein, α-1 acid glycoprotein, hepcidin, malaria, hookworm infestation, syphilis and Helicobacter pylori infection were assessed. Setting: Antenatal care clinic at Kawempe Health Centre, Kampala, Uganda. Subjects: HIV-negative women (n 151) in their fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 64 publications
5
31
3
Order By: Relevance
“…In addition, the high burden of iron deficiency during pregnancy in this study could be due to the fact that, in Uganda as a whole, 32% of women of reproductive age are anemic before pregnancy [7] mainly as a result of iron deficiency. Similar findings were also reported by studies from Central Uganda [14] and parts of Portugal [18] among first trimester pregnant women in which the prevalence of iron deficiency was 40.4% and 38.3% respectively. Results of this study were also consistent with what was reported in a systematic review done among pregnant women in Ethiopia, Kenya, Nigeria and South Africa in which the prevalence of iron deficiency ranged from 19-61% [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the high burden of iron deficiency during pregnancy in this study could be due to the fact that, in Uganda as a whole, 32% of women of reproductive age are anemic before pregnancy [7] mainly as a result of iron deficiency. Similar findings were also reported by studies from Central Uganda [14] and parts of Portugal [18] among first trimester pregnant women in which the prevalence of iron deficiency was 40.4% and 38.3% respectively. Results of this study were also consistent with what was reported in a systematic review done among pregnant women in Ethiopia, Kenya, Nigeria and South Africa in which the prevalence of iron deficiency ranged from 19-61% [19].…”
Section: Discussionsupporting
confidence: 90%
“…The Kish-Leslie formula [13] was used to calculate the sample size of the study. A29.1% prevalence of anemia during pregnancy was used to calculate a sample size of 320 participants [14]. A consecutive sampling technique was used to enroll study participants.…”
Section: Sample Size and Sampling Proceduresmentioning
confidence: 99%
“…Several studies from different countries recently reported a positive association between H. pylori infection and iron deficiency anemia (IDA) [43][44][45], and several factors, including hypochlorhydria, pro-hepcidin, and hepcidin may possibly affect this hematological condition [45,46]. Another recent study also demonstrated a significant improvement of some IDA status indices, including mean corpuscular volume and transferrin, following H. pylori eradication in children from Egypt [47].…”
Section: Hematological Diseases Iron Deficiency Anemiamentioning
confidence: 99%
“…Hyperemesis gravidarum [8][9][10][11][12] Preeclampsia [13][14][15]23] Iron-deficiency Anemia [16][17][18][19] Intrauterine growth Restriction [20][21][22]27] Spontaneous abortion [24][25][26] and inflammatory damage over the gastric epithelium resulting in gastrointestinal disturbance such as hyperemesis gravidarum. H. pylori sequesters essential micronutrients from the host organism such as Iron (Fe) and it causes iron deficiency anemia.…”
Section: Referencementioning
confidence: 99%
“…Baingana et al [19] in a study whose aim is to describe the etiology of anemia en pregnant women in Uganda, analyzes iron deficiency and common infections as contributors to anemia in this particular population. They found that infections and inflammation are more relevant than iron deficiency in the etiology of Uganda´s pregnant women during the first quarter of the year.…”
Section: Iron-deficiency Anemiamentioning
confidence: 99%